2018
DOI: 10.30880/ijie.2018.10.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Activation of Clayey Soil Using Potassium Hydroxide & Fly Ash

Abstract: In this paper the potential of introducing alkali activated fly ash to a clayey soil as stabilizing agent was investigated. As alkaline activator Potassium hydroxide of 12 M was introduced to the soil fly ash mixtures. Unconfined compressive strength tests were carried out. Four different fly ash/solid ratios were proposed to be 10 %, 20 %, 30 % and 40 % at two curing regimes of 7 & 28 days. The highest unconfined compressive strength was of 40 % mixture recorded at 3.68 MPa after 28 days. Alkaline activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Similar trend was observed by Teing et al [24]. The reason for this improvement are the microstructural changes (such as uptake, re-condensation and the presence of glassy phase) taking place in the mixture fabric during the stabilization process [22][23][24][25]. Scanning Electron Microscopy SEM showed that voids between soil particles were almost filled with structured aluminosilicate polymerized gel.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar trend was observed by Teing et al [24]. The reason for this improvement are the microstructural changes (such as uptake, re-condensation and the presence of glassy phase) taking place in the mixture fabric during the stabilization process [22][23][24][25]. Scanning Electron Microscopy SEM showed that voids between soil particles were almost filled with structured aluminosilicate polymerized gel.…”
Section: Introductionsupporting
confidence: 81%
“…Scanning Electron Microscopy SEM showed that voids between soil particles were almost filled with structured aluminosilicate polymerized gel. Therefore, discrete particles of the geopolymer composite material exhibit a denser and more closely bound texture [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Razali et al [20] claimed that a Peat stabilised by Vinyl Acetate-Acrylic copolymer (VAAC) in an amalgam of sand, lime and cement may produce satisfactory results. An alkali activated flyash stabilised soil also demonstrated high UCS value after 28 days curing [21].…”
Section: Introductionmentioning
confidence: 91%
“…it also increases the brittleness of soil significantly. This issue is comparable to soils subjected to treatment with cement and lime, which increase strength since aluminium-silicate hydrate (ASh) is the cementitious agent in cement, and calciumsilicate hydrate (CSh) is the cementitious agent in lime [38][39][40][41].…”
Section: Introductionmentioning
confidence: 97%